New Lexicons in the Lao Language - Chanthao, Rattana (Journal of Mekong Societies, 2014)
Lexical increase and decrease are general phenomena of living languages and are associated with social change. The Lao People’s Democratic Republic (Laos PDR) changed the form of administration in 1975, and in recent years the country has opened up and developed in many ways. Language research can demonstrate changes in social phenomena as well increases in the number of lexicons or words in a society. This article aimed to find new Lao words and organize them into semantic fields. The data were collected from Lao mass media, including magazines, newspapers, and television programs published or broadcast in 2012-2013. These new words do not appear in Lao dictionaries. The research discovered 978 new words in the Lao language that can be organized into 15 semantic fields, in decreasing order of frequency: verbs, society, personality, economics, food, education, administration, places, idioms, technology, mass media, sports, transportation, nature, and colors. Most of them are borrowed from Thai, demonstrating the influence of Thai language in Laos.